Accelerated Aging in Cancer and Cancer Treatment: Current Status of Biomarkers - Soniya Abraham; Jay Parekh; Seohyuk Lee; Humayra Afrin; Mariya Rozenblit; Kim R. M. Blenman; Rachel J. Perry; Leah M. Ferrucci; Jessica Liu; Melinda L. Irwin; Maryam Lustberg (Cancer Medicine, 2025)
ABSTRACT Background Aging in humans is a heterogeneous process influenced by both biological and chronological factors. Biological age reflects an individual's physiological reserve and functional status. Increasing evidence suggests that cancer and its therapies accelerate biological aging. Many biomarkers have been evaluated to assess the biological age of patients with cancer. These biomarkers are emerging as potential tools to predict cancer‐related toxicity and an individual's functional capacity as well as to individualize treatment. Methods This review summarizes the current literature on aging biomarkers in cancer patients, with a focus on markers of cellular senescence and epigenetic modification. We evaluate the existing evidence supporting their use as predictors of toxicity in patients undergoing chemotherapy and radiation therapy. Results Biomarkers such as interleukin‐6 (IL‐6), leukocyte telomere length (LTL), and DNA methylation age show potential for assessing biological age, frailty, and functional reserve. The expression of p16INK4A has demonstrated promise in predicting therapy‐induced toxicity and making treating decisions. However, additional confirmatory studies are necessary to further validate these biomarkers before they can be utilized as decision aids. Conclusion Aging biomarkers hold promise for individualizing cancer therapy and predicting treatment‐related toxicity. However, further studies are essential to validate their reliability and support their integration into clinical practice.